Effectiveness of using 2D atlas and 3D PDF as a teaching tool in anatomy lectures in initial learners: a randomized controlled trial in a medical school - Fatma Sıla Eroğlu; Beyza Erkan; Sevil Buket Koyuncu; Zeynep Rumeysa Komşal; Feray Ekin Çiçek; Müşerref Ülker; Merve Ebrar Toklu; Melike Atlan; Yavuz Selim Kıyak; Serdar Kula; Özlem Coşkun; Işıl İrem Budakoğlu (BMC Medical Education, 2023)
Abstract Background Anatomy is a crucial part of medical education, and there have been attempts to improve this field by utilizing various methods. With the advancement of technology, three-dimensional (3D) materials have gained popularity and become a matter of debate about their effectiveness compared to two-dimensional (2D) sources. This research aims to analyze the effectiveness of 3D PDFs compared to 2D atlases. Methods This study is a randomized controlled trial involving 87 Year-1 and Year-2 medical students at Gazi University Faculty of Medicine, Turkey. The study was conducted in two steps. In Step-1, students were randomized to watch lecture videos on liver anatomy and male genitalia anatomy supplemented with either a 3D PDF (intervention group) or 2D atlas (control group) images. Following the video lectures, a test (immediate test) was administered. In Step-2, the same test (delayed test) was administered 10 days after the immediate test. The test scores were compared between the intervention and control groups. In addition to the descriptive analyses, Chi-square and Mann-Whitney U tests were performed. Results In the immediate test, while there was no significant difference between the groups for the liver test (p > 0.05), 3D PDF group’s scores (Median = 24.50) was significantly higher than the 2D atlas group’s in the genitalia test (Median = 21.00), (p = 0.017). The effect size (Cohen’s d) was 0.57. In the delayed test, there was no significant difference between the groups in the liver and genitalia tests (p > 0.05). However, the effect size in the immediate genitalia test was 0.40. Year-1 students’ immediate test of genitalia performances were significantly higher in the 3D PDF group (Median = 24.00) than the 2D atlas group (Median = 19.00), (p = 0.016). The effect size was 0.76. Also, Year-1 students’ 3D PDF group (Median = 20.50) presented with significantly higher performance than the 2D atlas group (Median = 12.00), (p = 0.044) in the delayed test of genitalia, with the 0.63 effect size. Conclusion 3D PDF is more effective than 2D atlases in teaching anatomy, especially to initial learners. It is particularly useful for teaching complex anatomical structures, such as male genitalia, compared to the liver. Hence, it may be a valuable tool for medical teachers to utilize during lectures.